2019
DOI: 10.1007/s10439-019-02410-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Changes in Airflow and Energy Loss in a Progressive Tracheal Compression Before and After Surgical Correction

Abstract: The energy needed to drive airflow through the trachea normally constitutes a minor component of the work of breathing. However, with progressive tracheal compression, patient subjective symptoms can include severe breathing difficulties. Many patients suffer multiple respiratory comorbidities and so it is important to assess compression effects when evaluating the need for surgery. This work describes the use of computational prediction to determine airflow resistance in compressed tracheal geometries reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that tracheal airflow is dominated by the jet emanating from the glottis and more extensive upstream anatomy does not affect the tracheal WOB or resistance. 11,25 The inlets were held at a constant pressure for each simulation. In vivo, the pressure in the nasopharynx will change during inhalation, but the pressure loss in the trachea is relative to this so the tracheal component of the WOB will not be affected by neglecting the nasal geometry.…”
Section: Cfd Simulation-boundary Conditionsmentioning
confidence: 99%
“…Previous studies have shown that tracheal airflow is dominated by the jet emanating from the glottis and more extensive upstream anatomy does not affect the tracheal WOB or resistance. 11,25 The inlets were held at a constant pressure for each simulation. In vivo, the pressure in the nasopharynx will change during inhalation, but the pressure loss in the trachea is relative to this so the tracheal component of the WOB will not be affected by neglecting the nasal geometry.…”
Section: Cfd Simulation-boundary Conditionsmentioning
confidence: 99%
“…Lung mechanics research has delivered multiscale modelling methods to study both health and pathophysiology [ 1 ]. Studies have characterized the architecture and function of the upper airways [ 2 , 3 , 4 ], the tree-like airway structure and its mechanics [ 5 , 6 , 7 , 8 , 9 , 10 ] with its tight coupling to the circulatory system [ 11 ], and the smallest air-containing units of the lung: the alveoli [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that during an epidemic crude CFR estimation becomes an underestimate of the actual CFR [5]. However, because of both limited numbers of test and presence of asymptotic or mild cases, there exists unreported cases [25][26][27][28]. Therefore, after further adjustment for reporting rates lower than 50%, estimated CFRs became less than one-third compared to crude CFR, and survival interval adjusted CFR.…”
Section: Discussionmentioning
confidence: 99%